Determinants, Interests and Potential Risks: A Systematic Review of Corporate Water Responsibility Management - Peng, Xuhui (Journal of business ethics, 2025)
The escalating global water crisis has driven increased academic attention on corporate water responsibility management (WRM). However, research into corporate WRM remains limited and fragmented, and a holistic understanding of WRM is lacking. Hence, to increase the awareness on WRM, we systematically reviewed 105 research articles from the Scopus and Web of Science databases, spanning years 2004-2024. Through this review, we identified key determinants, interests, potential risks, and opportunities for future research from the existing literature. Moreover, we constructed an integrated framework offering a holistic perspective. Essentially, while WRM is emerging as a critical area of study, there is an urgent need for both deeper academic exploration and greater corporate engagement. This review provides a complete picture of existing WRM research and outlines clear directions for future quantitative and qualitative studies.